Students’ Perceptions of Difficulties in Learning Basic Kanji at Pakuan University and Darma Persada University - Alo Karyati; Kun Makhsusy Permatasari; Yessy Harun (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to examine the perceptions of Japanese Literature students at Pakuan University and Darma Persada University regarding the difficulties encountered in learning basic-level kanji. Kanji is a type of character originating from China that was introduced to Japan. It is also one of the subjects often considered a daunting and most challenging obstacle for Japanese language learners, particularly beginner students. The difficulties in learning kanji are generally caused by the students' background as users of the Roman alphabet (romaji), which poses challenges when studying kanji. This study employed a descriptive quantitative approach, with data collection techniques utilizing a Likert scale distributed via Google Forms to students from both universities. The research participants consisted of 31 students from the Japanese Literature Study Program at Pakuan University and 54 students from the Japanese Language and Culture Study Program at Darma Persada University who had completed the basic kanji course. The results indicated that students experienced primary difficulties in memorizing kanji forms and meanings, distinguishing between onyomi and kunyomi, and applying kanji within the context of jukugo (compound kanji). Furthermore, learning strategies, motivational factors, and the support of the kanji instructional materials used also influenced students' difficulties in learning kanji. These findings are expected to contribute to the development of more effective kanji learning strategies and serve as constructive input for educators in determining basic-level kanji learning models.